2014
DOI: 10.1002/aic.14542
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput packed‐bed microreactors with in‐line analytics for the discovery of asphaltene deposition mechanisms

Abstract: in Wiley Online Library (wileyonlinelibrary.com)Understanding asphaltene nanoaggregation kinetics is a key to predicting the deposition in pure quartz-grain porous media. High-throughput quartz packed-bed microreactors (lPBRs) were, therefore, designed to provide mechanistic insights by merging oilfield chemistry and microchemical systems. In-line UV-Vis spectroscopy and pressure transducer were used to characterize the stable packing of quartz particles with porosity of $40% and permeability of $5.5 3 10 213 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 61 publications
2
59
0
Order By: Relevance
“…Hu et al showed that mechanical entrapment is the dominant mechanism for insoluble asphaltene deposition in a packed-bed device. 23,24 The dynamics of the deposition growth were governed by the relative contributions of convection and diffusion. The deposition profiles for the asphaltene aggregate at various times are shown in Figure 5.…”
Section: Dynamics Of Asphaltene Deposition Onto a Postmentioning
confidence: 99%
“…Hu et al showed that mechanical entrapment is the dominant mechanism for insoluble asphaltene deposition in a packed-bed device. 23,24 The dynamics of the deposition growth were governed by the relative contributions of convection and diffusion. The deposition profiles for the asphaltene aggregate at various times are shown in Figure 5.…”
Section: Dynamics Of Asphaltene Deposition Onto a Postmentioning
confidence: 99%
“…It has the advantages of better multiphase mixing and higher heat and mass transfer while maintaining the benefits of classical fixed beds: ease of fabrication, continuous flow, and catalyst immobilization . Because of these advantages, μPBRs have been applied in oxidation, hydrogenations, deprotection, fast catalyst screening, and synthesis of hazardous materials …”
Section: Introductionmentioning
confidence: 99%
“…Either the channel wall can then be rendered porous or a packing can be inserted in the microchannel. With an improper packing design this can however lead to a serious broadening of the RTD, but it can also give an opportunity to narrow the RTD as Hu et al demonstrated. While an initially empty microreactor (0.15 × 0.15 × 340 mm, 1.48–14.8 mm s −1 , 0.3–3 min) produced a Bodenstein number Bo = 52, Bo = 229 was observed after packing the microreactor with quartz particles of 20 to 40 µm.…”
Section: Plug Flowmentioning
confidence: 99%